O PROCESSO CRIADOR E SUA ABORDAGEM NA EDUCAÇÃO INFANTIL - GRAZIELE FRANCO (2021)
ABSTRACT This research aims to analyze and understand how psychosocial categories, games and games develop in childhood and their relationship with the creative process in early childhood education. To this end, it adopts the historical-cultural approach based theoretically on authors such as Vigotski (2009), Luria (1991), Kohan (2004) and Elkonin (2009). The results reveal that learning through playing is essential both for childhood development and for stimulating the creative process, helping to understand the world and the child's internal conflicts, and that the school and the teacher have a fundamental role in this. process. Keywords: Creative Process. Child education. Construction of the Subject.